Faktor-faktor yang Mempengaruhi Partisipasi Politik Penyandang Disabilitas Sebagai Calon Anggota Legislatif Pada Pemilu Tahun 2019 - Aji Pangestu; Leo Agustino; Antik Bintari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The emergence of political participation of persons with disabilities as Candidates for Legislative Members in the 2019 Election shows an increase in the quality of political participation, when viewed from the hierarchy of political participation, it shows an increase in political participation. This study wants to analyze what are the factors that encourage the increased political participation of persons with disabilities so that awareness will emerge as candidates for legislative members in the 2019 Election. This study was built using descriptive qualitative methods to describe what factors encourage political participation of persons with disabilities by analyzing the determinant factors so that awareness arises to advance as a candidate for legislative members in the 2019 Election. The results of this study indicate that only social characteristic factors do not have much influence in the nomination of persons with disabilities in the Indonesian Parliament in the 2019 Election. Then the political stimulants, personal characteristics, Democratic political situation and environment, and political education are very influential in the nomination of persons with disabilities in the Indonesian Parliament in the 2019 Election.